ANALISIS KARAKTERISRIK KARBON TONGKOL JAGUNG SEBAGAI PENDUKUNG KATALIS FUEL CELL DENGAN MENGGUNAKAN REAKTOR PIROLISIS TIPE FIXED BED - Danu Prasetyo (POLITALA PRESS, 2025)
Energy is a basic need that can support many things. Fossil energy accounts for 80% of the world's needs, this energy has an environmental impact. One of the new renewable energy (EBT), namely fuel cell, in its development has obstacles where the catalyst is expensive. This study aims to determine the characteristics of pyrolysis activated carbon as a catalyst supporting carbon fuel cell. corn cob waste is processed into activated carbon by being influenced by temperature and holding time. The temperature variation of the study was 400° and 500° with a residence time of 60 Minutes. The resulting carbon is tested proximate to determine the water content, ash content, volatiles, and bound carbon content. Based on the proximate test, the temperature variation of 400 ° produces the highest moisture content in the figure of 8.8% but still meets SNI No.06-3730-1995. The temperature variation of 500° produces the highest bound carbon at 74.35% in accordance with SNI No.06-3730-1995 so that it has the potential to support fuel cell catalysts.